2011
DOI: 10.1002/pmic.201000654
|View full text |Cite
|
Sign up to set email alerts
|

Implications of high‐temperature events and water deficits on protein profiles in wheat (Triticum aestivumL. cv. Vinjett) grain

Abstract: Increased climatic variability is resulting in an increase of both the frequency and the magnitude of extreme climate events. Therefore, cereals may be exposed to more than one stress event in the growing season, which may ultimately affect crop yield and quality. Here, effects are reported of interaction of water deficits and/or a high-temperature event (32°C) during vegetative growth (terminal spikelet) with either of these stress events applied during generative growth (anthesis) in wheat. Influence of comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
108
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(112 citation statements)
references
References 43 publications
3
108
0
Order By: Relevance
“…Hurkman et al (2009) observed increases in individual protein spots of up to 8.5-fold while Majoul et al (2004) reported increases as high as 19-fold when high temperatures were applied throughout much of grain development. In comparison, changes generally were less than 2.5-fold when high temperatures were applied early in grain development (Laino et al, 2010;Yang et al, 2011). Most changes in the levels of proteins in response to drought were less than 3-fold (Hajheidari et al, 2007;Yang et al, 2011) and changes in response to fertilizer generally were less than 4-fold .…”
Section: Proteomic Analysis Of Non-gluten Proteinsmentioning
confidence: 95%
See 3 more Smart Citations
“…Hurkman et al (2009) observed increases in individual protein spots of up to 8.5-fold while Majoul et al (2004) reported increases as high as 19-fold when high temperatures were applied throughout much of grain development. In comparison, changes generally were less than 2.5-fold when high temperatures were applied early in grain development (Laino et al, 2010;Yang et al, 2011). Most changes in the levels of proteins in response to drought were less than 3-fold (Hajheidari et al, 2007;Yang et al, 2011) and changes in response to fertilizer generally were less than 4-fold .…”
Section: Proteomic Analysis Of Non-gluten Proteinsmentioning
confidence: 95%
“…In comparison, changes generally were less than 2.5-fold when high temperatures were applied early in grain development (Laino et al, 2010;Yang et al, 2011). Most changes in the levels of proteins in response to drought were less than 3-fold (Hajheidari et al, 2007;Yang et al, 2011) and changes in response to fertilizer generally were less than 4-fold . Of the 134 proteins noted in Table 2, 46 showed changes in more than one study and 20 showed changes in response to both temperature and drought.…”
Section: Proteomic Analysis Of Non-gluten Proteinsmentioning
confidence: 95%
See 2 more Smart Citations
“…in northern China) is thought to be that of soil water stress (Ma et al 2007). Water stress is known to influence dry matter production as well as quality of wheat (Yang et al 2011). Drought promotes HMW-GS accumulation in the early grain filling stage, whereas the opposite effect occurs at late grain filling (Jiang et al 2009).…”
mentioning
confidence: 99%